Recent research trends in the rational design strategies of carbon-based electrocatalysts for electrochemical ammonia synthesis - Hyojung Lim; Jinuk Choi; Euihyeon Hwang; Sathyanarayanan Shanmugapriya; Gnanaprakasam Janani; Subramani Surendran; Heechae Choi; Gibum Kwon; Kyoungsuk Jin; Uk Sim (Carbon Trends)
Ammonia electrosynthesis is the most sustainable way to produce carbon-free hydrogen carriers, which would pave the way for the foreseen hydrogen economy and carbon neutralization as it has the potential to replace the conventional Haber-Bosch process. The electrocatalytic production of ammonia, which renewable energy resources could drive, reduces the carbon footprint contribution to fossil fuel consumption. Moreover, ammonia electrosynthesis also paves the way for recycling industrial/chemical wastewater and NO emissions. Hence, the advancement of electrocatalytic ammonia synthesis techniques is highly mandated for a greener future. This review consolidates the recent research trends associated with carbon-based electrocatalysts, which could elevate this viable technology with cost-effectiveness.